The Role of Varahamihira in the Evolution of Astronomy and Astrology: A Literary and Cultural Study of Kampil's Influence (Integral Research, 2024)
Ancient Indian astronomy and astrology owe much of their development to the great intellect of Varahamihira from the 6th century CE. Because of his great works, like Pancha-siddhantika, Brihat Samhita and Brihat Jataka, his ideas reached deep into ancient Indian sciences and daily life. This study conducts research on Varahamihira’s life, explores how he changed the study of astronomy and examines the influence of his birthplace, Kampil (today part of Uttar Pradesh), on his learning and ongoing effects. Trying to link historical texts, archeological finds and cultural tales, we hope to better understand how Varahamihira and Kampil influenced one another. A careful study of his main texts reveals that he used concepts from America, Greece and Persia to develop a distinguished way of looking at the cosmos. Additionally, the paper points out that Kampil was a prosperous cultural and academic place, thanks to its unique atmosphere, during the Gupta era. Using information from various sources – texts, museum finds and popular tales – we explore the role Kampil may have had on Varahamihira’s science. His books illustrate that he understood the world’s processes, plus the values and culture of his own time. In this way, the research aims to value Varahamihira’s legacy by connecting it to the broad and vibrant world of Indian scholarship, particularly Kampil’s cultural play. This approach confirms that his writings on these subjects remain important.
Keywords: Varahamihira, Evolution of Astronomy, Kampil, Pancha-siddhantika, Brihat Samhita, Brihat Jataka.